Liquid air energy storage – Analysis and first results from a pilot scale demonstration plant. (1st January 2015) - Morgan, Robert; Nelmes, Stuart; Gibson, Emma; Brett, Gareth
Highlights: A novel cryogenic energy storage system is proposed. Classical and full cycle analysis is used to describe the process and determine the cycle efficiency. Results from the testing of a pilot scale prototype are presented. Scale up of the process and the characteristics of a commercial scale unit are discussed. Abstract: Energy storage is an important technology for balancing a low carbon power network. Liquid Air Energy Storage (LAES) is a class of thermo-electric energy storage that utilises a tank of liquid air as the energy storage media. The device is charged using an air liquefier and energy is recovered through a Rankine cycle using the stored liquid air as the working fluid. The cycle efficiency is greatly improved through the storage and recycling of thermal energy released during discharge and used to reduce the work required to liquefy air during charging. Analysis and results from the design and testing of novel LAES concept at pilot scale are presented. Fundamental analysis of the LAES cycle is first described to determine the theoretical cycle performance and in particular the value of cold recycle. The pilot plant is then described together with the results of a series of comprehensive technical and commercial trials. The paper concludes with a discussion on the future potential of LAES in particular the fit with the requirements for bulk energy storage and the transition of the LAES technology from pilot to commercial scale.